A PRELIMINARY STUDI ON TREES AND ROAD INFRASTRUCTURE CONFLICTS IN PADANG CITY WEST SUMATERA INDONESIA - marsia pela; Afrizal Afrizal; Reki Kardiman; Jabang Nurdin (UNIVERSITAS NEGERI PADANG, 2024)
Trees always appear as green building in a city, it growth side by side with various types of soild infrastructures and often ended with a conflict. Many cities in Indonesia experience the conflicts, especially between road and trees, which resulting risks to public and high restoration cost, but this urban green dynamic has not scientifically explored yet. We initiates a study on the dynamics of tree conflicts with road infrastructure in Padang City, a representative city in Indonesia with numerous conflict events. Species of tree, diameter, and distance to infrastructure were measured along 1.5 km of secondary and 1.5 km of primary road. There were 524 trees belong to nine species were found along 3 km road, and 35% of the trees were conflicted with the infrastructure. Primary road was dominated by small trees and was only causing 11% conflicts, while secondary road was dominated by large trees and 71% were conflicted. Number of conflict led by Pterocarpus indicus on both road types, while Swietenia mahogani was only conflicted with secondary road infrastructure and Dialium indum was only conflicted at primary road. Conflict of P. indicus at primary road was found at all diameter levels but at the secondary road the conflict was mostly associated to large trees. We also found many trees without conflict at all levels of diameter on both road types. Conflict of trees occurred at various distance to infrastructure and this found on both small and large trees. This study highlight that conflict between trees and infrastructure differed among species, size of tree diameter and conflict will always occurred when trees planted less than 2 m to infrastructure.